Optimization Automatic Irrigation Model for Urban Forests Based on Internet of Thing - Yani Prabowo; Wiwin Windihastuty; Jan Everhart R (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Irrigation is one of the important factors in the agricultural and plantation industries. In addition, irrigation is also important for watering city parks and urban forests. Irrigation is needed to maintain water availability. Based on this, proper water management efforts are needed, especially for irrigation that is carried out conventionally because it is inefficient so that it requires a lot of water that does not match the needs. Conventional irrigation also takes a lot of time just to irrigate plants so that it is less effective for large and relatively large areas. For this reason, technology is needed that automatically carries out irrigation effectively and efficiently. This community service aims to be implemented in the Pondok Labu city forest which currently requires automatic watering to make it easier to carry out irrigation which can later be monitored. The system used in this study is automatic irrigation based on the Internet of Things (IoT). Automation uses Arduino Mega Pro Mini and other supporting components. Watering can be done automatically according to schedule or if the soil conditions are dry and stop watering on soil that shows moisture. Automatic irrigation can also be monitored using a smartphone by utilizing a smartphone application.